Michaelis Pselli Chronographia - Reinsch, Diether Roderich (Millennium-Studien / Millennium Studies, 2014)
The new critical edition of Michael Psellos` Chronographia takes into account the entire scholarly work on this text since 1874 in a critical apparatus and a separate text-critical commentary. Compared to previous editions, it provides an improved text, suggesting many new readings. Comprehensive indices facilitate the search within the Greek text. The German translation appears in the Sammlung Tusculum.